Body image satisfaction in freshmen college students in physical education courses SATISFAÇÃO COM A IMAGEM CORPORAL EM ACADÊMICOS INGRESSANTES EM CURSOS DE EDUCAÇÃO FÍSICA - Claumann G.S.* (2014)
This study aimed to investigate body image satisfaction and the associated factors in freshmen college students in Physical Education courses. Participated 149 (88 men) freshmen college students in Physical Education courses of a public university from Florianopolis/SC. Were collected sociodemographic information (sex, age, marital status and economic level), anthropometric (body mass and stature) and related to body image (figure rating scale). A high proportion of students dissatisfied with body image (79.2%) was observed, with greater dissatisfaction by overweight (53.0%). Boys pointed silhouettes of numbers 4 and 5 as ideal (78.4%), while girls preferred silhouettes 3 and 4 (75.4%). Girls and students with overweight presented, respectively, three and 14 times more chances of dissatisfaction by overweight when compared to boys and eutrophic. Most students were dissatisfied with body image, with an association with sex and weight status.